Lateral marketing : - Kotler, Philip (John Wiley & Sons, Inc., 2003)
Rather than perpetuating the vertical marketing practice of segmentation, two marketing specialists offer a framework for generating new products and services to meet marketing gaps. An example given by Kotler (Northwestern U.) and Trias de Bes (Barcelona) is of getting computer-less consumers to shop online. Annotation ©2004 Book News, Inc., Portland, OR (booknews.com)